Participación del metabolismo de los esfingolípidos en los procesos de proliferación y diferenciación celular - Udovin, Lucas Daniel (2018)
Sphingosine kinase (SphK) is a key enzyme in the lipid metabolism because it regulates the transition of sphingosine to sphingosine-1-phosphate (S1P). S1P is intended as a key lipid in cellular processes such as: proliferation, apoptosis and cell survival. However, little is known about the role of this enzyme in the process of cellular differentiation. This doctoral thesis proved that the controlled inhibition of SphK activity by two SphK inhibitors (L-threo-Dihydrosphingosine and SKI-II) caused: a decrease in the cellular proliferation in MDCK cells, with arrest at the G0/G1 stage of the cell cycle. This cell cycle arrest was accompanied by a nuclear accumulation of cyclin D1 and hypophosphorylation of Rb protein. Moreover, SphK inhibition induced an increase in the percentage of cell in G0 phase at the expense of a decrease in G1 stage (G1-G0 transition) accompanied of an increase in the sphingolipid synthesis. On the other hand, SphK inhibition produces morphological changes in actin cytoskeleton and in the distribution of proteins constituting cell tight and adherens junctions, as well as, an increase in the gene expression of E-cadherin and cadherin-16 (epithelial differentiation markers) corresponding to a transition towards a more differentiated cellular phenotype.